Gravity Models of Internal Migration – the Czech Case Study - Monika Jandová; Tomáš Paleta (Review of Economic Perspectives, 2015)
In this paper, the models of internal migration flows between regions (NUTS 3) in the Czech Republic in time series from 1991 to 2012 are tested. The paper aims to find out how size, distance and economic variables explain migration flows between Czech regions. Several versions of an extended gravity model were used for testing, where economic factors which are frequently mentioned in literature on migration were used as regressors (i.e. average wage, registered unemployment rate, job vacancies and job vacancies per applicant). Internal migration flow is the dependent variable. In comparison to the pure gravity model, the extending of models with the economic variables improves the results of the models only slightly. The results show that the highest explanatory value of migration is given by models with rates of the variables tested.
Keywords: 330